2018
DOI: 10.1093/heapol/czy032
|View full text |Cite
|
Sign up to set email alerts
|

Technical quality of delivery care in private- and public-sector health facilities in Enugu and Lagos States, Nigeria

Abstract: Private-sector providers are increasingly being recognized as important contributors to the delivery of healthcare. Countries with high disease burdens and limited public-sector resources are considering using the private sector to achieve universal health coverage. However, evidence for the technical quality of private-sector care is lacking. This study assesses the technical quality of maternal healthcare during delivery in public- and private-sector facilities in resource-limited settings, from a systems an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Furthermore, this study indicates higher interventionism levels in the private sector than in the public one and, in turn, perceived OV is also higher in the private sector [20]. Thus, we should reflect on the technical and human quality of such healthcare in the private health sector, which falls in line with what other authors have reported [44]. This consideration is reinforced by the results obtained for the mixed healthcare type included in the present research work.…”
Section: Of 13supporting
confidence: 85%
“…Furthermore, this study indicates higher interventionism levels in the private sector than in the public one and, in turn, perceived OV is also higher in the private sector [20]. Thus, we should reflect on the technical and human quality of such healthcare in the private health sector, which falls in line with what other authors have reported [44]. This consideration is reinforced by the results obtained for the mixed healthcare type included in the present research work.…”
Section: Of 13supporting
confidence: 85%
“…In many instances, when there are limited functional PHC facilities within communities, the private sector fills the service delivery gap in the form of for-profit services (for those who can afford it), non-profit services (by non-governmental organisations [NGOs] and faith-based organisations sometimes aimed at individuals who cannot pay for services) and informal service providers. 135 , 136 To improve health care at the PHC level, state governments could strategically secure funding for health systems development with international donors and NGOs in addition to their federal allocation (including specifically for health, guaranteed through the legislative change that centralised PHC governance at the state level). 137 , 138 Although foreign funding is not sustainable, with evidence-based planning and foresight, programmes supported by international NGOs and bilateral or multilateral organisations can lead to sustainable health system improvements by establishing health system infrastructure, especially technical and physical infrastructure.…”
Section: Section 4: Health System Reform—a Pathway To Universal Healt...mentioning
confidence: 99%
“…In keeping with our recommendations of localising particular aspects of health services provision, it is important to allocate more funds at the state and local government levels for purchasing health services, with evidence-based, strategic, and appropriately-tracked spending 137 to ensure resources are used efficiently while removing financial barriers to access by reducing out-of-pocket expenditure in both absolute and relative terms. 136 Innovative strategies are also needed to enable potential beneficiaries, especially in the informal sector, to better comprehend and accept the concept of prepayment methods of financing health care, and ensure all the formal sector employees are adequately informed about the Formal Sector Social Health Insurance Programme of the NHIS. State and local governments can establish a tax-based health financing mechanism targeted at vulnerable groups, the poorest groups, and individuals working in the informal sector of the economy to accelerate progress towards universal health coverage.…”
Section: Section 5: Investing In the Future Of Nigeria—health For Wealthmentioning
confidence: 99%
“…The Nigerian private health sector provides an estimated 60% of maternal, newborn and child health (MNCH) services (eg, institutional delivery, antenatal care, routine immunisation, contraceptives) 6. A higher percentage of women deliver in private health facilities in the southeast (eg, Imo State 71% and Anambra State 53%) than the northwest or northeast 7. Faith-based organisations, like the Christian Health Association of Nigeria, provide a significant proportion of maternal and child health services across all levels of care (ie, primary, secondary and tertiary), serving both rural populations and the urban poor 8.…”
Section: Introductionmentioning
confidence: 99%
“… 6 A higher percentage of women deliver in private health facilities in the southeast (eg, Imo State 71% and Anambra State 53%) than the northwest or northeast. 7 Faith-based organisations, like the Christian Health Association of Nigeria, provide a significant proportion of maternal and child health services across all levels of care (ie, primary, secondary and tertiary), serving both rural populations and the urban poor. 8 Nurses and midwives tend to run small, for-profit clinics and maternity homes that are patronised by low-income and middle-income populations located in periurban, rural and underserved communities.…”
Section: Introductionmentioning
confidence: 99%